Clinically important age-related differences in sleep related disordered breathing in infants and children with Prader-Willi Syndrome. - Michal Cohen; Jill Hamilton; Indra Narang (PLoS ONE, 2014)
BACKGROUND: Sleep related disordered breathing (SDB) in pediatric Prader-Willi Syndrome is gaining increased attention due to the possible association of growth hormone therapy, SDB and sudden death. However data on the patterns of SDB and their management, particularly in infants in this population, is lacking. OBJECTIVE: The aim of this study was to 1) describe patterns of SDB in growth hormone naive infants with PWS and the management of these disorders in our institution 2) Compare the patterns of sleep disorders between infants and children with PWS. METHODS AND DESIGN: Polysomnograms of infants and children (0-18 years of age) with Prader-Willi Syndrome were reviewed. Age, sex, anthropometrics, sleep architecture, obstructive and central apnea indices and oxygen saturations were recorded. Data of infants with central sleep apnea treated with oxygen were analyzed to evaluate the efficacy of this treatment. The main outcome measures were obstructive and central apnea indices on a polysomnogram. RESULTS: Data of 44 patients, 23 under 2 years of age and 21 older children were included. Infants when compared with older children were more likely to experience central sleep apnea (43% vs. 5%; p = 0.003). In older children obstructive was significantly more prevalent than central sleep apnea. Supplemental oxygen was used to treat 9/23 infants with central sleep apnea. Oxygen therapy resulted in a significant decrease in the median central apnea index from 14 (5,68) to 1 (0,6; p = 0.008) events/hour and an improvement in the oxygen saturation nadir from 70% (52, 92) to 81% (64, 95; p = 0.080). CONCLUSIONS: Central sleep apnea with associated oxygen desaturations is more prevalent in infants compared with older children with Prader-Willi Syndrome. Supplemental oxygen was efficacious in treating central sleep apnea in infants. Routine sleep surveillance for all children with Prader-Willi Syndrome and treatment with oxygen for central sleep apnea should be considered.